De-Secularizing Legal Education in Indonesian Non-Islamic Law School: Examining The ‘Introduction to Jurisprudence’ Textbooks on The ‘Norm Classification’ Chapter - Fajri Matahati Muhammadin; Hanindito Danusatya (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2018)
The Indonesian legal system is not secular, but the legal education in non-Islamic universities are secular. This article will highlight the ‘Introduction to Jurisprudence’ course (ITJ) at law undergraduate programs. More specifically, one chapter will be analyzed i.e. ‘Classification of Norms’ because it is an early fundamental chapter in ITJ which shapes the jurisprudential reasoning of the law students. This article uses a literature study to observe the most used textbooks for the (ITJ) course in the top law schools in Indonesia. It will be found that the approached used by these textbooks are secular and incompatible with the Indonesian non-secular legal system. Islamization of knowledge is needed to ‘de-secularize’ this ‘Classification of Norms’ chapter.